KOMPOSISI UKURAN DAN POLA PERTUMBUHAN IKAN CAKALANG (Katsuwonus pelamis) DI PERAIRAN KEPULAUAN TANIMBAR - Danyel selwanus Fuatkait; Erica J. Baesardy; Anaci Batlajery (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2024)
Skipjack tuna (katsuwonus pelamis) is a fishery resource that has economic value which is in great demand and is utilized with various fishing tools and methods. This research aims to describe the skipjack tuna fishing unit using trolling rods, and analyze the distribution of length and weight of skipjack tuna in the waters of the Tanimbar Islands. The research was carried out from February to April 2024 in the waters of the Tanimbar Islands. Data collected through observation and interviews as well as practice of the fishing process, catches were measured by total length and the relationship between length and weight, then analyzed descriptively qualitatively, using the Sturges formula and length and weight. The results of the research show that the type of equipment and fishing method operated in the form of multiple hand line, and skipjack tuna caught in the waters of the Tanimbar Islands are in the size of 29.5-75 cm TL where the percentage of presence shows that the size of 49-52 cm dominates, namely 35. 62% with negative allometric skipjack tuna growth patterns.